1995
DOI: 10.1074/jbc.270.29.17148
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Pathways of Gi- and Gq-mediated Mitogen-activated Protein Kinase Activation

Abstract: Receptors that couple to the heterotrimeric G proteins, Gi or Gq, can stimulate phosphoinositide (PI) hydrolysis and mitogen-activated protein kinase (MAPK) activation. PI hydrolysis produces inositol 1,4,5-trisphosphate and diacylglycerol, leading to activation of protein kinase C (PKC), which can stimulate increased MAPK activity. However, the relationship between PI hydrolysis and MAPK activation in Gi and Gq signaling has not been clearly defined and is the subject of this study. The effects of several sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

18
321
4
3

Year Published

1997
1997
2000
2000

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 418 publications
(346 citation statements)
references
References 50 publications
18
321
4
3
Order By: Relevance
“…The resultant activation of Ras can lead to the activation of ERK though Raf-MEK pathway (Rocca et al, 1997). This is consistent with the observation that the bg-activated ERK is not sensitive to PKC-inhibitors but sensitive to Ras, Raf and tyrosine kinase inhibitors (Hawes et al, 1995). Gbg-activation of PLC can also lead to an increase in DAGs and subsequently to the activation of PKC.…”
Section: The Bg-subunitssupporting
confidence: 91%
See 2 more Smart Citations
“…The resultant activation of Ras can lead to the activation of ERK though Raf-MEK pathway (Rocca et al, 1997). This is consistent with the observation that the bg-activated ERK is not sensitive to PKC-inhibitors but sensitive to Ras, Raf and tyrosine kinase inhibitors (Hawes et al, 1995). Gbg-activation of PLC can also lead to an increase in DAGs and subsequently to the activation of PKC.…”
Section: The Bg-subunitssupporting
confidence: 91%
“…Results from these studies indicated that the expression of the Gb1g1, Gb1g2, Gb1g3, and Gb2g2-configurations increased the basal levels of ERK by 6 ± 10-folds while the con®gurations involving Gb3 or Gb4 failed to activate ERK. Similarly, only the Gb1g1, Gb1g2, Gb1g3, and Gb2g2 con®gurations stimulated 3 ± 4-fold increase in PI hydrolysis suggesting their activation of PI-PLC pathways (Hawes et al, 1995). Coexpression of a dominant negative mutant of Ras along with the Gbg completely inhibited the activation of ERK without having any e ect on PLC activity.…”
Section: The Bg-subunitsmentioning
confidence: 93%
See 1 more Smart Citation
“…EMALA et al [94], confirming the observations of others [75,82], recently showed in human cultured airway smooth muscle cells that activation of Ras by ET was blocked by pertussis toxin, suggesting that the receptors for ET, which activate Ras, couple Gi but not Gq. Furthermore, in the same study, overexpression of a G protein bc-subunit scavenger failed to prevent activation of Ras, indicating that ET receptors most probably couple to a Gi that activates Ras via the Gia subunit [94] and not a Gibc (or Gqbc) subunit as proposed in other cell types [92,95] (fig. 3).…”
Section: Extracellular Signal-regulated Kinase Activation By G Proteimentioning
confidence: 67%
“…Gi or Go) [90,91] or pertussis toxininsensitive (i.e. Gq) [92] G-protein-coupled pathways, which are dependent on the activation of either PKC [50,92] or Ras proteins [90,91,93]. EMALA et al [94], confirming the observations of others [75,82], recently showed in human cultured airway smooth muscle cells that activation of Ras by ET was blocked by pertussis toxin, suggesting that the receptors for ET, which activate Ras, couple Gi but not Gq.…”
Section: Extracellular Signal-regulated Kinase Activation By G Proteimentioning
confidence: 99%